2015
DOI: 10.1093/femsec/fiv171
|View full text |Cite
|
Sign up to set email alerts
|

Abundance and potential metabolic activity of methanogens in well-aerated forest and grassland soils of an alpine region

Abstract: Although methanogens were recently discovered to occur in aerated soils, alpine regions have not been extensively studied for their presence so far. Here, the abundance of archaea and the methanogenic guilds Methanosarcinales, Methanococcales, Methanobacteriales, Methanomicrobiales and Methanocella spp. was studied at 16 coniferous forest and 14 grassland sites located at the montane and subalpine belts of the Northern Limestone Alps (calcareous) and the Austrian Central Alps (siliceous) using quantitative rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 50 publications
2
14
0
7
Order By: Relevance
“…At our study site, strong decreases of microbial abundance and activities from alpine to subnival and further to nival soils were observed, with bacteria decreasing at higher elevations than archaea (Hofmann et al 2016a). A distinct impact of the specific type of vegetation on the abundance of methanogenic archaea and on their potential to form methane within upland soils was found across the Tyrolean Alps (Hofmann et al 2016c).…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…At our study site, strong decreases of microbial abundance and activities from alpine to subnival and further to nival soils were observed, with bacteria decreasing at higher elevations than archaea (Hofmann et al 2016a). A distinct impact of the specific type of vegetation on the abundance of methanogenic archaea and on their potential to form methane within upland soils was found across the Tyrolean Alps (Hofmann et al 2016c).…”
Section: Introductionmentioning
confidence: 58%
“…To determine the exact abundance of the five dominant groups of methanogenic archaea (Methanosarcinales, Methanobacteriales, Methanococcales, Methanomicrobiales, and Methanocellales) and to avoid biased results because of interactions, we used a spiking method described in Hofmann et al (2016c). Only the abundance of Methanocella is shown separately in the results because it may stand for the copy number of all methanogenic archaea, and was the only group that was found in all soil samples of a study investigating more than thirty sites across Tyrol (Hofmann et al 2016c). For more details concerning the microbial parameters measured along the elevation gradient of our site, see Hofmann et al (2016b).…”
Section: Soil Characteristicsmentioning
confidence: 99%
“…The rationale of applying higher methane concentrations is that in previous studies it was shown that methane production potentials reached up to 1 % CH 4 (Hofmann et al 2016;Praeg et al 2014;Wagner et al 2012). Thus, it was of our interest to study whether the influences of temperature, plants, and bedrock type on net methane balance are changed or remain under elevated methane concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…The upland forest soils harbor populations of methanogens. Thus, the upland forest soils can become net sources of methane especially when water content increases (Megonigal and Guenther, 2008; Hofmann et al, 2016). Since pH values of pine-dominated forest soils typically range between 3 and 4 (Lau et al, 2007; Megonigal and Guenther, 2008; Machacova et al, 2016), which is below the pH optimum of many cultured methanotrophs (Hanson and Hanson, 1996), acid adaptation of methanotrophs needs to be adequately characterized to evaluate methane oxidation in upland forest ecosystems.…”
Section: Introductionmentioning
confidence: 99%